Are Banks Really Lazy? : Evidence from Middle East and North Africa - Gray, Simon; Karam, Philippe; Turk-Ariss, Rima. (Washington, D.C. : International Monetary Fund, 2014)
We investigate whether low loan-to-deposit (LTD) ratios and high levels of reserve balances at the central bank (or holdings of government securities) are a reflection of policy-driven factors compared to commonly cited reasons of reluctance to lend or sometimes weak investment demand in uncertain environments. We examine changes to central bank (CB) balance sheet structures as well as commercial banks' flow of funds over the period 2007-2012. First, Middle East and North Africa (MENA) CBs play an active role in view of their size that is very large with respect to their economies compared to CBs in advanced economies. Second, under exchange rate targeting, most MENA CB balance sheets are asset-driven, holding foreign exchange (FX) reserves to support the exchange rate policy and resulting in lower loan-to-deposit (LTD) ratios in the case of unsterilized increases in FX. Third, CB policy decisions seem to be accompanied by an increase in commercial bank reserve money balances, with ensuing reduction in the LTD. Finally, if governments meet their financing needs from the banking system-whether from commercial banks or by monetary financing-commercial bank balance sheets will tend to expand, resulting in lower LTD ratios. Our analysis suggests that government and CB actions may also drive the demand for and supply of credit, which are traditionally attributed to the behavior of banks and non-financial corporates and households only. The findings offer a different interpretation of changes in CB and banks' balance sheets, with direct implications for LTD, calling to exercise caution in recommending policy action which aim at propping up LTD to 'appropriate' levels in an effort to reinvigorate credit following a downturn.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet